Popular Apostasy and Religions of the Fatherland in Antonio Gramsci’s Notebook 20 - Lucas, Marie; Frosini, Fabio (International Gramsci Journal, 2024)
Gramsci predicted very early in his work the imminent demise of Catholicism. In the very first phase of writing his Quaderni del carcere, however, he focused on the triumph of the Holy See thanks to the 1929 Lateran Accords, a source of important financial and institutional privileges for the Church. Based on a detailed study of the composition and variants of Notebook 20, this article examines Gramsci's later reflections on the future of the Church and his diagnosis of the decline of Catholicism. His review of the internal struggles between integral Catholics, Jesuits, and modernists reveals a relative rehabilitation of the latter through the figure of Ernesto Buonaiuti. Particularly noteworthy is Gramsci's analysis of the heretical fate of Catholic lay organisations and the reactionary scope of social Catholicism, which was designed to stem the tide of popular movements. Gramsci also linked the rise of religious indifference to the growing success of European nationalism, particularly of German racist ideology in the mid-1930s.